A Study of the Ethical Issues of Private Entrepreneurs Participating in Politics in China - Tian, Zhilong (Journal of business ethics, 2008)
Since the 16th National Congress of Communist Party of China (16th NCCPC) in 2002, more and more private entrepreneurs have appeared on the political arena in China. The article first describes the state of the phenomenon, and analyzes the reasons and the related ethical issues of private entrepreneurs participating in politics. For this purpose, the article begins by suggesting a framework of analyzing the ethical analysis of corporate political actions, then applies it to a case study of the phenomenon, and finally, makes some policy suggestions to the government for regulating the practice of private entrepreneurs’ involvement in politics.